THE EFFECT OF WORM DISEASES ANIMATION VIDEO INTERVENTION ON ELEMENTARY SCHOOL STUDENT'S KNOWLEDGE AND ATTITUDES LEVEL IN SAMPALAN KLOD VILLAGE, KLUNGKUNG REGENCY - Widyantara, I Komang Alit; Swastika, I Kadek; Diarthini, Ni Luh Putu Eka; Sudarmaja, I Made (E-Jurnal Medika Udayana; Vol 13 No 07 (2024): E-Jurnal Medika Udayana, 2024)
One of the diseases that often attack children is helminthiasis. The prevalence of  Soil-Transmitted Helminths  (STH) infection in Bali is still quite high (10.1-31.7%). One of the control efforts that can be done is the provision of health promotion using animated video media to increase children's knowledge and attitudes. This study aimed to determine the effect of animation video intervention about helminthiasis on the level of knowledge and attitudes among elementary school students in Sampalan Klod Village. This study used a quasi-experimental method with a pre-test and post-test group design with control and used total 120 students that came from grades IV, V, and VI at SDN 1 and SDN 2 Sampalan Klod. Respondents were selected using non-probability sampling with a purposive sampling method and data analysis was done using the Wilcoxon test. The results showed that there was a significant difference between the level of knowledge and attitudes before and after intervention in the experimental group. The difference in the mean value of knowledge is 29.45 with Sig. (2-tailed) of 0.000 (p-value < 0.05). As for the attitude, the difference in the mean is 19.22 with p-value < 0.05. In conclusion, the intervention of worm animation video affects the level of knowledge and attitudes among elementary school students regarding STH infection. It is hoped that this research can be a source of data in developing worm prevention and control programs in children   Keywords : Animation video, Knowledge level, Attitude, Soil Transmitted Helminths (STH)